A new quantum chaotic cuckoo search algorithm for data clustering - Ishak Boushaki, Saida; Kamel, Nadjet; Bendjeghaba, Omar (Expert systems with applications, 2018)
•Quantum chaotic cuckoo search algorithm is proposed for the data clustering problem.•The performance of the proposed approach was assessed on six well known datasets.•The Chaos maps and Boundary handling strategy enhance the cuckoo search algorithm.•The nonhomogeneous quantum update improves the global search ability.•The significant superiority of the proposed algorithm over eight recent algorithms. This paper presents a new quantum chaotic cuckoo search algorithm (QCCS) for data clustering. Recent researches show the superiority of cuckoo search (CS) over traditional meta-heuristic algorithms for clustering problems. Unfortunately, all the cuckoos have identical search behaviours that may lead the algorithm to converge to local optima. Also, the convergence rate is sensitive to initial centroids seeds that are randomly generated. Therefore, the main contribution of this paper is to extend the CS capabilities using nonhomogeneous update inspired by the quantum theory in order to tackle the cuckoo search clustering problem in terms of global search ability. Also, the randomness at the beginning step is replaced by the chaotic map in order to make the search procedure more efficient and improve the convergence speed. In addition, an effective strategy is developed to well manage the boundaries. The experimental results on six famous real-life datasets show the significant superiority of the proposed QCCS over eight recent well known algorithms including, genetic quantum cuckoo search, hybrid cuckoo search and differential evolution, hybrid K-means and improved cuckoo search, standard cuckoo search, quantum particle swarm optimization, differential evolution, hybrid K-means chaotic particle swarm optimization and genetic algorithm for all benchmark datasets in terms of internal and external clustering quality.